Pengukuran Kesiapan Pengguna Aplikasi Face to Face Polsek Semboro Menggunakan Metode TRI (Technology Readiness Index) - Yanuar Nurdiansyah; Ahmad Dwi Jayanto (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2021)
The government has a mandate to provide excellent services to the community. So, improving the quality of public services is a major agenda. As the Semboro police station did by launching an application called “Face to Face Polsek Semboro” at October 23rd, 2021. It is an innovation from Polsek Semboro to ease Semboro community in making of loss reports in the era of the covid-19 pandemic. This study aims to measure the user readiness of the “Face to Face Polsek Semboro” using Technology Readiness Index (TRI) model. This research was conducted by interview, designing the instrument, and performing the validity and reliability tests. When the instrument passed the tests, it is distributed to the respondents. The obtained data was analyzed to calculate the level of user readiness and to provide recommendations. Based on the results of the study, it is known that the Optimism variable gives the largest score compared to the Discomfort, Innovativeness, and Insecurity. The obtained TRI Score is 3.178 and classified as medium category (Medium Technology Readiness).